CORRELATION BETWEEN READING INTEREST WITH RESULT OF STUDY - Natalia Natalia Natalia (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This research aims to find out whether there is a positive and significant correlation between the interest to read the results of the study grade V SD Tingkir Tengah 02 school year 2017/2018 Salatiga. The subject of this research is the grade V SD Tingkir Tengah 02 Salatiga a number of 30 persons. The variable in this study is of interest as a free variable, and read the results of the study as a bound variable. Data collection is done using the now as well as documentation of student learning outcomes. Technique of data analysis is a test using SPSS correlations.Based on the correlation of the test has been performed, the obtained value of 0.36 significance which means that value greater than 0.05 meaning not correlated. Interest in reading and learning results also had a negative correlation with the value of the degrees of correlation -385, * which declared negative. Values, 383 * entered into the range value of 0.21 up to 0.41, meaning the interest to read the results of the study have a weak correlation.